Two patients with ZAP-70 deficiency in China present with a different genetic, immunological, and clinical phenotype - Xianze Luo; Qing Liu; Lina Zhou; Xuemei Tang; Xiaodong Zhao; Zhiyong Zhang (BMC Pediatrics, 2023)
Abstract Zeta(ζ)-Chain Associated Protein Kinase 70 kDa (ZAP-70) deficiency is a rare autosomal recessive primary immunodeficiency disease. Little is known about this disease. In this study, we report two patients to extend the range of clinical phenotypes and immunophenotypes associated with ZAP-70 mutations. We describe the clinical, genetic, and immunological phenotypes of two patients with ZAP-70 deficiency in China, and the data are also compared with the literature. Case 1 presented with leaky severe combined immunodeficiency with low to the absence of CD8 + T cells, while case 2 suffered from a recurrent respiratory infection and had a past medical history of non-EBV-associated Hodgkin’s lymphoma. Sequencing revealed novel compound heterozygous mutations in ZAP-70 of these patients. Case 2 is the second ZAP-70 patient presenting a normal CD8 + T cell number. These two cases have been treated with hematopoietic stem cell transplantation. Selective CD8 + T cell loss is an essential feature of the immunophenotype of ZAP-70 deficiency patients, but there are exceptions. Hematopoietic stem cell transplantation can provide excellent long-term immune function and resolution of clinical problems.